Risk factors for type 2 diabetes mellitus among out-patients in Ho, the Volta regional capital of Ghana: a case–control study - Horlali Yao Gudjinu; Bismark Sarfo (BMC Research Notes, 2017)
Abstract Background The prevalence of type 2 diabetes mellitus in developing countries like Ghana continues to rise. This study seeks to assess the risk factors of type 2 diabetes mellitus in a Ghanaian setting. An unmatched case–control study among patients receiving care at the out-patient departments of the two major hospitals in the Ho Municipality. Patients diagnosed with type 2 diabetes mellitus were recruited. Appropriate controls with similar ages who were also patients receiving care at the out-patient department of these hospitals were recruited. Both cases and controls were administered a questionnaire that comprises of standardized and validated tools. These tools include WHO STEPs instrument, general practice physical activity questionnaire and rapid eating and activity assessment for patients. Additionally, the research participants were made to undergo physical examinations for weight, height, waist circumference and laboratory testing of fasting venous blood to assess the biochemical factors of interest namely fasting blood glucose and fasting lipids. Analysis of data was done using STATA version 11. Results A total of 136 (48 cases and 88 controls) participants of which 95 [39 (81.25%) cases and 56 (63.64%) controls] respondents underwent laboratory testing for fasting blood glucose and fasting blood lipid (total cholesterol, HDL cholesterol and triglycerides). Participants were aged between 35 and 62 years. This study reveals a number of risk factors for type 2 diabetes mellitus. Individuals in the middle socio-economic class have a greater risk of developing type 2 diabetes mellitus with an OR of 5.03 (p < 0.003; 95% CI 1.71–14.74). Eating large quantities/servings of fruits per seating provides protection against development of type 2 diabetes mellitus. A low physical activity level is a valid determinant of type 2 diabetes mellitus irrespective of body mass index, socio-economic level or place of residence. Conclusions Individuals within the middle socio-economic level, who are physically inactive and do not consume large amounts of fruit are at greatest risk of developing type 2 diabetes mellitus. Living in a rural setting is attendant with high levels of physical activity this tends to protect rural residents from type 2 diabetes mellitus. Physical activity level confounds the relationship between place of residence and development of type 2 diabetes mellitus. Local policies should be realigned to attract individual of the middle socio-economic level to live in rural areas where they are more likely to be both physically active and consume more fruits thus averting the risks of developing T2DM.